Accounting for fair value and its impact on the efficiency of financial performance of Sudanese banks A field study - اىٍدرس اىدنخٔر غٍر اىصر اىحصَ ٌحٍد; اىٍدرس اىٍصاغد زِاٌ٘ار زِشطاز احٍد (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
This research problem is represented in the fact that, notwithstanding, the unique characteristics of the fair value accounting, proved by the international experiences of the utilization of this trend; numerous Sudanese banks have no interest in the fair value accounting in order to measure its assets and liabilities and disclose the same in banks' financial reports. In this regard, some research studies have proved the lack of conformity of the accounting measurement according to the historical cost under high inflation rates, taking into account the existence of high inflation rates in the Sudan, which may affect the financial performance of banks. To put said facts into effect the research problem has been put forward in the following research questions: What is the effect of the fair value accounting on the financial performance efficiency of the Sudanese banks? Does accounting measurement according to the basis of the fair value accounting, affect the financial performance efficiency of the Sudanese banks? Does accounting disclosure according to the basis of the fair value accounting, affect the financial performance efficiency of the Sudanese banks? The research aimed to analyze the effect of application of the fair value accounting on the financial performance efficiency of the Sudanese banks, by introducing the unique characteristics of the fair value accounting and its significance and to clarify the effect of accounting measurement and disclosure according to the basis of the fair value on the financial performance efficiency of the Sudanese banks. The research employed the analytical descriptive approach to effect the analysis of the 100 questionnaire forms, distributed to the research community, using the statistical package for the social sciences (SPSS) to analyze the data in order to know the answers of the respondents towards the questionnaire statements. The research proved the hypotheses and reached a number of research findings, including the following: The Sudanese banks are so interested in the fair value accounting in measuring and disclosing its assets and liabilities in the financial reports. Accounting measurement and disclosure according to the fair value accounting, has helped the Sudanese banks improve its financial performance in a sound manner